MECKEL’S DIVERTICULUM AS A CAUSE OF ACUTE STRANGULATED SMALL BOWEL OBSTRUCTION (A CASE REPORT) - Duzhyi, Ihor; Metynskyi, Serhii; Lamakh, Oleh; Kurochkin, Oleksandr; Lohutov, Vitalii (Eastern Ukrainian Medical Journal, 2026)
Meckel’s diverticulum is the most common congenital anomaly of the gastrointestinal tract. One of its rare and potentially life-threatening complications is strangulated small bowel obstruction caused by a mesodiverticular band, which may lead to intestinal ischemia and necrosis.Objective. To present a clinical case of acute strangulated small bowel obstruction caused by a mesodiverticular band of Meckel’s diverticulum and to analyze diagnostic and surgical management features.Materials and Methods. A clinical case of a 26-year-old patient admitted with signs of acute mechanical bowel obstruction is described. Diagnosis was based on clinical findings, abdominal radiography, and intraoperative assessment.Results. During surgery, Meckel’s diverticulum connected to the mesentery of the small intestine by a fibrous mesodiverticular band was identified. The band caused torsion of the ileum with strangulated small bowel obstruction. No signs of bowel ischemia were detected. After division of the band, bowel passage was restored. Due to the small size of the diverticulum and absence of inflammatory changes, diverticular peritonization without bowel resection was performed. The postoperative period was uneventful.Conclusions. Strangulated small bowel obstruction caused by a mesodiverticular band of Meckel’s diverticulum is a rare condition with nonspecific clinical manifestations. Timely surgical intervention helps prevent bowel ischemia and allows organ-preserving treatment.